2006
DOI: 10.1002/dvg.20256
|View full text |Cite
|
Sign up to set email alerts
|

Genetic targeting of principal neurons in neocortex and hippocampus of NEX-Cre mice

Abstract: Conditional mutagenesis permits the cell type-specific analysis of gene functions in vivo. Here, we describe a mouse line that expresses Cre recombinase under control of regulatory sequences of NEX, a gene that encodes a neuronal basic helix-loop-helix (bHLH) protein. To mimic endogenous NEX expression in the dorsal telencephalon, the Cre recombinase gene was targeted into the NEX locus by homologous recombination in ES cells. The Cre expression pattern was analyzed following breeding into different lines of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
702
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 507 publications
(731 citation statements)
references
References 38 publications
(45 reference statements)
28
702
1
Order By: Relevance
“…eCB functions specifically underpinning pyramidal cell progenitor proliferation were elucidated in mice with conditional deletion of CB 1 Rs through Cre recombinase expressed under the control of regulatory sequences of NEX, a neuronal basic helix-loop-helix protein (15) (CB 1 R f/f,NEX-Cre ). Prominent Cre activity is observed by approximately E11.5 in cortical progenitors in NEX-Cre mice (15), ensuring the lack of CB 1 Rs in pyramidal cells at all developmental stages studied here. In these mutants (16), VZ/SVZ progenitor proliferation was significantly impaired, as indicated by reduced Ki67 and GOLGA5 cell density in proliferative zones ( Fig.…”
Section: Cb1r Expression In Developingmentioning
confidence: 52%
See 1 more Smart Citation
“…eCB functions specifically underpinning pyramidal cell progenitor proliferation were elucidated in mice with conditional deletion of CB 1 Rs through Cre recombinase expressed under the control of regulatory sequences of NEX, a neuronal basic helix-loop-helix protein (15) (CB 1 R f/f,NEX-Cre ). Prominent Cre activity is observed by approximately E11.5 in cortical progenitors in NEX-Cre mice (15), ensuring the lack of CB 1 Rs in pyramidal cells at all developmental stages studied here. In these mutants (16), VZ/SVZ progenitor proliferation was significantly impaired, as indicated by reduced Ki67 and GOLGA5 cell density in proliferative zones ( Fig.…”
Section: Cb1r Expression In Developingmentioning
confidence: 52%
“…We assessed the in vivo significance of our findings in CB 1 R f/f,NEX-Cre mice (15). In new-born CB 1 R f/f,NEX-Cre (Fig.…”
Section: Cb1r Deletion Reveals Fasciculation Deficitsmentioning
confidence: 97%
“…This result suggests that competition may play a role, but because global NR1 knockouts have severely compromised viability (they have reduced body weight, and none survive pass weaning) we cannot rule out compensatory effects. Additionally, the NEX promoter drives CRE expression as early as E11.5 (17), as compared with the postnatal viral infection, which could also account for the differences. Future work, perhaps with specific inducible CRE lines of mice (16), should be able to carefully separate the cell-autonomous role of NMDA receptor function from any part it has in comparing the afferent activity of competing axons.…”
Section: Resultsmentioning
confidence: 99%
“…To separate Sip1's function in early cortical progenitor cells from its role in postmitotic neurons, we used a Nex-cre approach. Previous studies have found that the majority of cells that produce Cre driven by the Nex promoter are nondividing neurons, whereas only a very small fraction are proliferative 16,20 . Moreover, immunostaining of Nex-driven Cre and neuronal HuC/D in the neocortex showed an almost complete overlay of both at E14.5 ( Supplementary Fig.…”
Section: Sip1 Levels Are High In Postmitotic Neocortical Cellsmentioning
confidence: 99%
“…To investigate the function(s) of Sip1 in the developing neocortex (beginning at E11.5), we analyzed loxP/Cre-based conditional knockout mice. We deleted Sip1 in either the entire mouse CNS (using a Nestin-cre approach), dorsal telencephalic precursors (Emx1-cre) or dorsal telencephalic postmitotic cells (Nex-cre) [15][16][17] . We found that specific ablation of Sip1 in the neocortex led to a temporal shift in corticogenesis, mediated by premature feedback signaling from cortical plate neurons to progenitor cells via Ntf3 and Fgf9.…”
mentioning
confidence: 99%